2016
DOI: 10.3847/0004-637x/830/2/77
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stellar Flares on the Chemical Composition of Exoplanets and Spectra

Abstract: More than three thousand exoplanets have been detected so far, and more and more spectroscopic observations of exoplanets are performed. Future instruments (JWST, E-ELT, PLATO, Ariel, . . . ) are eagerly awaited as they will be able to provide spectroscopic data with a greater accuracy and sensitivity than what is currently available. This will allow more accurate conclusions to be drawn on the chemistry and dynamics of the exoplanet atmospheres, on condition that the observational data are processed carefully… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 71 publications
2
94
1
Order By: Relevance
“…The effect of such large variations in the stellar ionizing flux may be significant, especially early in the life of the star and planetary system. The previous studies examining the impact of stellar flares on exoplanet atmospheres, like Segura et al (2010) and Venot et al (2016), used only UV observations, ignoring the potential increase in UV emission incident on the planet due to high-energy photons in the manner described in Smith et al (2004). Hence they are underestimates at best of the impact of these flares on exoplanet atmospheric chemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of such large variations in the stellar ionizing flux may be significant, especially early in the life of the star and planetary system. The previous studies examining the impact of stellar flares on exoplanet atmospheres, like Segura et al (2010) and Venot et al (2016), used only UV observations, ignoring the potential increase in UV emission incident on the planet due to high-energy photons in the manner described in Smith et al (2004). Hence they are underestimates at best of the impact of these flares on exoplanet atmospheric chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…One critical open question in this area is whether the scalings observed in solar eruptive events between photons and particles holds during stellar events. A more recent paper on the effects of stellar flares on exoplanetary atmospheres (Venot et al 2016) determined that planets around very active stars would likely never achieve a steady state due to the frequent photon bombardment of the exoplanetary atmosphere from stellar flares. Smith et al (2004) considered the transport of ionizing radiation in terrestrial exoplanet atmospheres, and found that while a thick atmosphere can protect the planetary surface from incident X-rays and γ-rays, up to 4% of the incident ionizing radiation received at the surface in the 2000-3200 Å wavelength range comes from atmospheric transmission and reprocessing of the high-energy radiation.…”
Section: Discussionmentioning
confidence: 99%
“…That complex flare event on AD Leo, which has by chance very similar light curve shape to the largest flare seen in the K2 light curve of TRAPPIST-1, has an amplitude of V ≈ 0.5 magnitude. Venot et al (2016) concluded, that atmosphere of the two super-Earth-like hypothetical planets, that would orbit AD Leo, would be altered irreversibly and significantly after such eruption. Their model suggests that the post-flare steady state would only return on the scale of ≈ 30000 years, thus, the planetary atmosphere would be constantly altered by eruptions due to the high flaring rate.…”
Section: The Complex Flare Event At Hjd 2457812mentioning
confidence: 99%
“…Strong overlying magnetic fields likely confined the eruption (Sun et al 2015;Thalmann et al 2015). As more exoplanetary atmosphere models consider the important influence of stochastic flares (Lammer et al 2007;Segura et al 2010;Airapetian et al 2016;Venot et al 2016), improving constraints on the fluxes and energies of associated particles is necessary.…”
Section: Flares and Energetic Particlesmentioning
confidence: 99%